Novel miniaturized fabry-perot refractometer based on a simplified hollow-core fiber with a hollow silica sphere tip - Hu, Dora Juan Juan (2013)
In this paper, we report and demonstrate a novel miniaturized intrinsic Fabry-Perot interferometer (IFPI) based on a simplified hollow core fiber ended with a hollow silica sphere tip. The hollow core fiber is spliced to single mode fiber and subsequently applied with fusion arc at the end, forming a hollow sphere with a thin silica wall. The reflection spectrum is modulated by the environment of the sensor head such as refractive index and temperature. By monitoring and measuring the fringe visibility, the measurement of refractive index of the calibrated solution is carried out experimentally. The achievable refractive index (RI) resolution is about 6.2 × 10-5 by measuring the fringe visibility. This sensor offers key features and advantages of IFPI including easy fabrication, low loss, low cost, and good fringe visibility. Furthermore, the sensor head is made of single material and therefore has the potential for measurements in harsh environments. Measurements at high temperatures up to ~ 1000°C are carried out. Results reveal that the sensor has low temperature.